(untitled) (Talenta Conference Series: Science and Technology (ST), 2019)
Trace matriks ialah jumlah dari elemen diagonal utama dari matriks kuadrat. Penelitian ini membahas mengenai jejak kekuatan bilangan bulat positif matriks nyata 2x2. Ada dua langkah dalam membentuk bentuk umum dari trace matriks. Pertama, tentukan bentuk umum (An) dan buktikan menggunakan induksi matematika. Kedua, tentukan jejak bentuk umum (An) dan buktikan dengan bukti langsung. Hasilnya diperoleh bentuk umum jejak daya bilangan bulat positif dari matriks nyata 2x2 nyata untuk n ganjil dan n genap. Trace matrix is ​​the sum of the main diagonal elements of the square matrix. This Paper discusses the trace of positive integer power of real 2x2 special matrices. There are two steps in forming the general shape of the trace matrix. First, determine the general form of (An) and prove it using mathematical induction. Second, determine the general form trace (An) and prove it by direct proof. The results obtained a general shape of trace of positive integer power power of real 2x2 special matrices for n odd and n even.